Análise do processo de desenvolvimento de produtos de confecções de Apucarana com base em um modelo de referência - Leal, Letícia Sanches (2021)
It’s noticeable that the textile industry has advanced a lot during the last decades. Multiple new segments and different products were created, from new lining technologies to new types of fabric for well-known articles. An efficient product development process (PDP) became essential for companies in order to maintain their competitiveness in a fast-changing market. In this context, it’s necessary to use a reference model with systematized stages for the product development process. Therefore, it aims to analyze the product development process from Apucarana’s textile industries based on the phases of Rozenfeld’s et al., (2006), reference model. The present paper was done by using a qualitative research method of multiple cases study wherein were collected data from this Apucarana’s textile industries in order to contribute with the development of their own textile product development methodology.